MINERAL INDICATORS OF THE FORMATION CONDITIONS OF PALAEODELTAS IN VERKHOYAN IN THE CARBONIFEROUS PERIOD - Yapaskurt O.V.; Kosorukov V.L.; Zolotarev D.A. (My University, 1996)
A study was made of Carboniferous deltaic deposits from Verkhoyan. The study was based on an analysis of the composition and typomorphic characteristics of the mineral parageneses in the deposits. This was accompanied by a step by step analysis of the post-sedimentational new formations in the rocks. The deposits were taken from the North of the Orulgan Range in the Dzhardzhan - Ulakhan-Unguokhtakh interfluve. This analysis of the initial material composition of the Late Palaeozoic formations in Verkhoyan produced the same conclusions about the conditions under which the deltaic deposits were formed as lithological-facies reconstructions carried out previously by the authors.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная